Process and Formulation Effects on Protein Structure in Lyophilized Solids using Mass Spectrometric Methods - Iyer, Lavanya K. (J Pharm Sci, 2016)
Myoglobin (Mb) was lyophilized in the absence (Mb-A) and presence (Mb-B) of sucrose in a pilot-scale lyophilizer with or without controlled ice nucleation. Cake morphology was characterized using scanning electron microscopy (SEM) and changes in protein structure were monitored using solid-state Fourier-transform infrared spectroscopy (ssFTIR), solid-state hydrogen-deuterium exchange-mass spectrometry (ssHDX-MS) and solid-state photolytic labeling-mass spectrometry (ssPL-MS). The results showed greater variability in nucleation temperature and irregular cake structure for formulations lyophilized without controlled nucleation. Controlled nucleation resulted in nucleation at ~ −5 °C and uniform cake structure. Formulations containing sucrose showed better retention of protein structure by all measures than formulations without sucrose. Samples lyophilized with and without controlled nucleation were similar by most measures of protein structure. However, ssPL-MS showed the greatest pLeu incorporation and more labeled regions for Mb-B lyophilized with controlled nucleation. The data support the use of ssHDX-MS and ssPL-MS to study formulation and process-induced conformational changes in lyophilized proteins.